1998
DOI: 10.1056/nejm199812243392603
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Trial of a Chest-Pain Observation Unit for Patients with Unstable Angina

Abstract: A CPU located in the emergency department can be a safe, effective, and cost-saving means of ensuring that patients with unstable angina who are considered to be at intermediate risk of cardiovascular events receive appropriate care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
200
1
17

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(224 citation statements)
references
References 17 publications
(13 reference statements)
6
200
1
17
Order By: Relevance
“…For example, with nonspecific chest pain, in addition to looking at observation use, one would need to look at ED discharge practices and proximate outcomes (e.g., 30-day missed acute myocardial infarction rate) to determine if the care pattern is safe and efficient. Although not directly studied, it is reasonable that an observation stay would be as safe as or safer than a similar inpatient admission as the duration in hospital is shorter and the quality of care has been shown to be equal or superior [1,2]. If observation care is not associated with worse in-hospital or proximate outpatient outcomes, then it may advance the value of health care delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, with nonspecific chest pain, in addition to looking at observation use, one would need to look at ED discharge practices and proximate outcomes (e.g., 30-day missed acute myocardial infarction rate) to determine if the care pattern is safe and efficient. Although not directly studied, it is reasonable that an observation stay would be as safe as or safer than a similar inpatient admission as the duration in hospital is shorter and the quality of care has been shown to be equal or superior [1,2]. If observation care is not associated with worse in-hospital or proximate outpatient outcomes, then it may advance the value of health care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in observation medicine has increased over the past decade, and the variety of clinical conditions considered suitable for observation has expanded from initial pathways for asthma and chest pain to a wider set of conditions such as transient ischemic attack and syncope [1,2]. Despite growing clinical research on observation protocols, there are no published data describing the utilization and variation of observation care for common emergency medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Marker protein measurements provide definitive diagnostic and prognostic information but take several hours after the onset of symptoms to become positive. This has led to the development of protocols in chest pain units in many centres to manage patients in the early hours after the onset of symptoms, and before a definitive diagnosis can be made [12,13]. A large proportion of patients who present to emergency departments with chest pain has non-cardiac diagnoses, and most of these would be, most appropriately, discharged directly home.…”
Section: Clinical Motivationmentioning
confidence: 99%
“…These have reduced the relative risk ranging from 6.5 to 25% in previous studies [4][5][6][7][8] . Previous records showed that use of these interventions in the setting of acute coronary syndromes (ACS) is still suboptimal, suggesting, upon admission, aspirin usage rates ranging from 91 to 92%, and upon discharge, ranging between 90 and 95%, statin usage upon discharge ranging between 26 and 57%, and beta-blocker usage upon discharge in less than 63 to 77% of patients [9][10][11][12][13][14] . The assessment of its occurrence, through a national registry for controlled collection recently implemented, can thus document the clinical practice in the treatment of patients with ACS, whether hospitalized in public and/or private hospitals in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Previous records showed that use of these interventions in the setting of acute coronary syndromes (ACS) is still suboptimal, suggesting, upon admission, aspirin usage rates ranging from 91 to 92%, and upon discharge, ranging between 90 and 95%, statin usage upon discharge ranging between 26 and 57%, and beta-blocker usage upon discharge in less than 63 to 77% of patients [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%